O movimento de ensinar e aprender álgebra no ensino fundamental - Trindade, Caroline Rodrigues (2018)
The following research derives of our concern about the learning of 7th grade students regarding the concept of Algebra, specifically, of first degree equations. In this sense, the study is supported in the theoretical-methodological fundaments of the Teaching Orientation Activity (TOA) to the organization of situations that trigger the learning related to the referred concept. We established as our research's main goal to investigate the learning of 7th grade students regarding first grade equations from the Teaching Orientation Activity's assumptions. With the purpose of reaching that goal, we planned the following investigative actions: research, in the historic logical movement, how was build the making of the first degree equation's concept and identify indications of learning expressed by the students. Because we understand that our research is an investigative one, we have established, also, a formative objective, which consists of organizing a learning space aimed at the appropriation of knowledge about first degree learning from the triggering learning situations. The research was developed with 35 students of Escola Municipal de Ensino Fundamental Teófilo Teodoro Streck, in the city of Novo Cabrais – RS. Initially, we did a brief theoretical incursion about the Mathematical Education and, also, a historical survey about Algebra. The theoretical and methodological reference follows the perspective of the Historical-Cultural Theory (VYGOTSKY), more specifically in the Theory of Activity (LEONTIEV) and the Teaching Orientation Activity (MOURA). The data were systematized from the planning of the situations that trigger the learning, the students' registers recorded in audio, video and photos, as well as the researching teacher's notes. For the data analysis, we defined four axes to the presentation of episodes and scenes (MOURA, 2004) that allowed us to verify indications of learning by the students. Seven learning-triggering situations were developed, which aimed to meet a conceptual nexus. We intend fort his work to contribute with the Mathematical Education area with the teaching and learning of Algebra, specially first degree equations, through situations that trigger the learning so that they enable the appropriation of the knowledge. The data analysis allows us to identify the importance of offering situations that trigger the learning who contemplate the conceptual links: fluency, variable, variation field and equality. Furthermore, they contribute in an effective way to the learning of students, the comprehension of the concept's logical-historical movement and the sharing of the developed actions.